PENGARUH SENAM KEGEL DAN PIJAT PERINEUM TERHADAP KEKUATAN OTOT DASAR PANGGUL LANSIA DI PUSKESMAS TABANAN III - Jayanti, Ayu (Coping: Community of Publishing in Nursing; Vol 3 No 2 (2015): JURNAL EDISI MEI-AGUSTUS 2015, 2015)
Elderly people are all over the age of 60 years with a variety of physical and non-physical changes due to aging. One of the physical changes that occur is a decrease in the strength of the pelvic floor muscles. Pelvic floor muscles can be measured with perineometer PFX2 set type. This study is a quantitative research model, the type of research is quasy experiment. Data collection was carried out on May 16 to July 4, 2014 against the elderly woman who actively participates in the activities of the elderly in health center III Tabanan. Sample of this research are 30 people by purposive sampling technique, the sample was divided into 2 groups: Kegel Exercise (15 people) and Perineum Massage (15 people). This study used the Paired T-Test for the analysis of the effect of Kegel Exercise, Wilcoxon Signed-Rank Test for the analysis of the influence of the Perineum Massage, and Mann-Whitney U Test to determine the effect of the Kegel Exercise and Perineum Massage on pelvic floor muscle strength of the elderly. The results of this study there was Kegel Exercise effect on muscle strength (p-value = 0.000, p <0.05), there was no effect of Perineum Massage on pelvic floor muscle strength of the elderly (p-value = 1.000, p> 0.05), and the mean Kegel Exercise (1.1333) is higher than the Perineum Massage (0.0667). Based on the results of this study are expected health workers in health centers III Tabanan may consider Kegel Exercise to prevent incontinence in the elderly.
Keywords: Elderly, pelvic floor muscle strength, Kegel Exercise, Perineum Massage